PENERAPAN ANALISA SWOT DALAM SISTEM PENDUKUNG KEPUTUSAN MANAJEMEN DI MUBAROK RESTO - Ahmad Mubaroq; Rita Wiryasaputra; Dwi Asa Verano (UNIVERSITAS INDO GLOBAL MANDIRI)
Information now become an absolute necessity for an organization or company to win a competition Along with the development of information needs, especially for restaurant owners to make decisions and to find out problems that occur in the restaurant, then developed an information system called decision support system. With decision support system information can be displayed in the form of a brief and displays the data in accordance with the needs so as to facilitate a restaurant owner in making decisions effectively, Problems that appear on Mubarok Resto that is not a system to help restaurant owners in making decisions on problems that occur in restaurants covers of internal and external factors of the restaurant.To overcome these problems is by applying SWOT analysis as a tool to analyze internal and external conditions in the development of decision support systems that specifically manage data information internal and external problems that occur in Mubarok Resto, the expected results of this research is to make a SWOT analysis application that can facilitate restaurant owners in making effective restaurant decisions.Keywords : Decision support system, SWOT, Management, Web applications.